2016
DOI: 10.1016/j.plipres.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acylation of proteins: The long and the short of it

Abstract: Long, short and medium chain fatty acids are covalently attached to hundreds of proteins. Each fatty acid confers distinct biochemical properties, enabling fatty acylation to regulate intracellular trafficking, subcellular localization, protein-protein and protein-lipid interactions. Myristate and palmitate represent the most common fatty acid modifying groups. New insights into how fatty acylation reactions are catalyzed, and how fatty acylation regulates protein structure and function continue to emerge. Myr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
244
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(250 citation statements)
references
References 155 publications
(164 reference statements)
4
244
0
2
Order By: Relevance
“…Furthermore, protein myristoylation is essential for parasite morphology and viability in protozoan parasites, including Leishmania and Trypanosoma brucei , and in Plasmodium species, which are the causative agents of malaria . The myristate moiety is involved in various biological processes, including protein–lipid and protein–protein interactions, membrane binding and activation . However, in many cases, the exact mechanism underlying these processes is not completely understood, and therefore, the development of specific molecular probes that can assist in identifying key interactions involving the myristate moiety is of considerable interest.…”
Section: Methodssupporting
confidence: 92%
“…Furthermore, protein myristoylation is essential for parasite morphology and viability in protozoan parasites, including Leishmania and Trypanosoma brucei , and in Plasmodium species, which are the causative agents of malaria . The myristate moiety is involved in various biological processes, including protein–lipid and protein–protein interactions, membrane binding and activation . However, in many cases, the exact mechanism underlying these processes is not completely understood, and therefore, the development of specific molecular probes that can assist in identifying key interactions involving the myristate moiety is of considerable interest.…”
Section: Methodssupporting
confidence: 92%
“…Neighboring fibroblasts were an excellent candidate for the source because some share intimate physical connections with AT2 cells (28), such as Pdgfrα-expressing 'lipofibroblasts' that support their production of surfactant and formation of alveolospheres in culture (17, 29, 30). Indeed, we found that the transmembrane protein Porcupine (Porcn), which catalyzes fatty acylation of Wnts and promotes their secretion (31) and is a putative marker of Wnt signaling niches (32), was expressed in rare alveolar stromal cells (Fig. 2a), most of which were Pdgfrα -expressing fibroblasts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous CoA thioesters are also involved in the post-translational modification of histones and thousands of other proteins (1)(2)(3)(4)(5). Three major subcellular CoA pools are found in the cytosol, mitochondria, and peroxisomes to support specific metabolic pathways (6,7).…”
Section: Introductionmentioning
confidence: 99%